Modeling Dahr el Baidar slope with an integrated geo-assessment - Rahhal, Muhsin (2015)
he slope of Dahr El Baidar located on the central mountain of Lebanon hosts a section of the Arab Highway that is under construction to connect Beirut to neighboring Arab countries. This slope has experienced failures and seismic movements, yet most involved geotechnical companies have investigated the slope with classical geotechnical procedures. In this paper, the slope analysis is an integrated approach to identify the principal causes of failure. Thus, the study includes geological, geophysical and geotechnical soil characterization of the designated area. The geological analysis reveals the presence of faults in the vicinity, in addition to a layer of weak clay at the surface. The geotechnical investigation is based on the interpretation of several boreholes for which quality assessment is carried out using in-situ sampling and lab tests. Geophysical tests are performed using ambient noise vibration technique with the Horizontal to Vertical Spectrum Ratio HVSR method, in order to reveal the resonant frequency and thickness of the subgrade material. The above data is used towards a better understanding of the cause and occurrence of the failing zone. It is suspected that the main triggering factor is water. Further analysis will be carried out to evaluate the effect of an earthquake loading. This work is part of the assessment and prediction of the behavior of various critical slopes in Lebanon carried by RUMMARE, a Research Unit on Mass Movement hazard Assessment and Risk Evaluation grouping researchers from major universities and research centers in Lebanon.